PENINGKATAN PARTISIPASI SISWA DALAM PEMBELAJARAN PPKN MELALUI PENERAPAN MODEL TAKE AND GIVE - Koko Enco Atma (Institut Pendidikan Indonesia, 2020)
This research generally aims to determine the level of students participation in learning process by using the Cooperative Learning model Take and Give types in increasing students participation in Regional Autonomy material in class IX E SMP Negeri 9 Tasikmalaya in the academic years 2017/2018. This research uses a class action method (action reseach) with data collection techniques through observation, carried out in two cycles. Each cycle consists of planning, action, observation and reflection. Data collected through observation of student activities and educator activities. The result of the first cycle of research, the value of the activity or participation of students in learning by 80.30%, while in the second cycle of 96.97%. Thus there has been an increase in the value of student activities in the learning process by 16.67%. The conclusion of this reseach can be formulated that the application of the cooperative learning model take and give types can increase the participation of students in learning on Regional Autonomy material in class IX E SMP Negeri 9 Tasikmalaya.